FENOMENA KOMUNIKASI ANGGOTA CALISTECHNIC DALAM MEMAKNAI TUBUH IDEAL DI KOTA PEKANBARU - Siregar, Nadiah; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Members of Calistechnic which is becoming a unique phenomenon is a form positive lifestyle and modern which is many followed by many artist and communities who are very concerned about appereance and healthy. In the all gymanastics studio in Pekanbaru Calistechnic become the only one weight loss exercise in the Kencana gymnastics studio Pekanbaru and PACS ( Pekanbaru Adiicted Calistechnic & StreetWorkout) the official community. This research aims to figure out the motives members of Calistechnic in the expressing ideal body, define ideal body of members Calistechnic in the city of Pekanbaru and experiences members of Calistechnic for expressing ideal body in the city of Pekanbaru.The research using qualitative methods within phenomenology approach. The informans are 10 members of Pekanbaru Calistechnic members who selected based on a purposive technique. The data collection techniques are in-depth interviews, participant observation and documentation. This research uses techniques of interactive data analysis that includes three phases, namely the reduction of the data, the presentasion of the data and the withdrawal of the conclusion.The result of this research show that motives of Pekanbaru Calistechnic members in expressing ideal body are motive the past (Because Motives) such as an existing hobby for a long time in the life Calistechnic members, and friends persuade for a followed Calistechnic and next motives of the future (in order to motive) Calistechnic members to get ideal body, as well communication media to invite the community for a healthy life and change the negative thoughts about Calistechnic members. The defition of Calistechnic members the deffeniti is media to expressing hoby and Calistechnic as and effort get a idela body and healthy. The communication exeriences of Pekanbaru Calistechnic members in expressing ideal body are fun experiences (positive) covers acceptance and support of the family, increase friendship, adding relationship, and confidence. The unpleasant experience (negative) covers has no achievements, shunned friend from other community, and considereddd disturbing the practice time.Keyword : Calistechnic ,Experiences, Experiences Communication, Ideal body